Survey peningkatan resiko penyakit DM di masa Pandemi covid-19 Di wilayah Kabupaten Ponorogo tahun 2021 - Heru Wiratmoko; Agus Wiwit Suwanto; Endang Purwaningsih (Indonesian Journal for Health Sciences, 2023)
DM is a chronic disease that cannot be cured but can only be reduced and blood sugar levels controlled. Blood sugar levels of DM patients can be controlled and reduced by pharmacological and non-pharmacological measures. The impact of the Covid 19 pandemic that can increase the risk of DM is stress. Stress due to the declining level of the community's economy can be due to losing a job, increasing the burden of living and others. At times of stress can increase levels of the hormone cortisol which can increase blood sugar levels. During the pandemic, people are afraid to leave the house so that activity decreases so that it will reduce the use of blood sugar by cells so that blood sugar increasesThe method used in this research is a survey by distributing a google form questionnaire with the link https://forms.gle/EsCR4qnoj62LZFnv9 via WA Online media to the community in the Ponorogo district from 6-15 October 2021 so that the number of respondents who fit the sample criteria is as much as 122 respondents. Measurement of DM risk factors using the FINDRISC questionnaire is a questionnaire that helps to identify the risk of DM disease.The results of the Survey on Increasing the Risk of DM Disease During the Covid 19 Pandemic in the Ponorogo Regency Region in 2021 it is known that from 122 respondents, 60 (49%) low risk respondents, 45 (36%) risk respondents slightly increased, 8 (7%) risk respondents medium, 8 (7%) high risk respondents and 1 (1%) very high risk respondents.